Project-Based Learning on Biotechnology Materials to Enhance High School Students' Creativity and Problem-Solving Skills - Galuh Rizky Amalia; Surti Kurniasih; Dadang Jaenudin (Universitas Pakuan, 2022)
This study aims to improve students' problem-solving abilities and creativity through project-based biotechnology learning. The research was conducted at a public high school in Gunung Putri, Bogor. This study involved students of class XI science which were divided into 2 groups, namely the experimental class and the control class. The research method used quasi-experimental with non-equivalent pretest-posttest control group design. The instruments used essays, questionnaires and observations. The results of this study are supported by the n-gain value of problem solving ability and creative thinking in the experimental class 0.73 (high) and the control class 0.53 (medium). Learning activities are very active and dynamic, students must communicate, be creative, think critically and collaborate. Student response was very enthusiastic. The conclusion of the research can be seen that project-based learning can improve problem solving and creativity of high school students.